دور الإطار التشريعي في إرساء معالم المالية الإسلامية في الجزائر: The role of the legislative framework in establishing the features of Islamic finance in Algeria - أسامة بوشريط (Journal of North African Economies, 2025)
The aim of this article is to clarify the legislations that have tackled Islamic finance in Algeria, focusing on awqaf, cooperative insurance, and Islamic banking. This exploration takes into account the recent willingness of authorities to embrace these financial approaches, as seen in civil and commercial laws, awqaf regulations, executive decrees related to cooperative insurance, and the guidelines set by the Algerian Central Bank. Hence, to promote Islamic finance and streamline its implementation. Findings show that Islamic finance in Algeria encounters several challenges related to regulatory framework, terminology comprehension, and the formulation and technical aspect of these financial operations. It suggests that the existing laws require enrichment and recommends that Algerian authorities draw upon the expertise of organizations such as the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Islamic Financial Services Board (IFSB) to further refine these legislations.